Metabolic rates, and not hormone levels, are a likely mediator of between‐individual differences in behaviour: a meta‐analysis. (7th November 2016) - Holtmann, Benedikt; Lagisz, Malgorzata; Nakagawa, Shinichi
Summary: Consistent individual differences in hormone levels and metabolic rates have been proposed to be potential state variables underlying consistent individual differences in behaviour (i.e. animal personality). However, it remains unclear whether either one alone or both of these potential state variables could be an underlying driver of animal personality. We address this question using meta‐analyses of published data from bird species. We hypothesized that state variables that mediate individual differences in behaviour would display similar or higher repeatability estimates than behavioural traits. To test this hypothesis, we quantified repeatability estimates of hormone levels, metabolic rates and behavioural traits. We found moderate to high mean repeatability estimates for both metabolic rates and behavioural traits, but low repeatability estimates for hormone levels. These findings indicate that metabolic rates likely represent an important mechanism for generating adaptive personality differences in behaviour. We also show that: (i) for hormones and behaviour, repeatability decreased with increasing interval time between two measurements; (ii) males and females differed in repeatability for behavioural traits; (iii) stress‐induced hormone levels were more repeatable than baseline levels. Future studies are now required to determine the direction of the association between metabolic rates and behavioural traits. At the same time, these studies should try to investigate which of the proposed mechanisms is responsible for the relationship between state variable and state‐dependent behaviour. In addition, we encourage researchers to report the coefficient of variation for between‐individual variance (CVB ) along with repeatability estimates because these two indices carry different information. We discuss how CVB may better facilitate future comparative studies, including meta‐analyses. A lay summary is available for this article. Abstract : Lay Summary